2022
DOI: 10.1177/00223433221078051
|View full text |Cite
|
Sign up to set email alerts
|

Co-ethnic bias and policing in an electoral authoritarian regime: Experimental evidence from Uganda

Abstract: Why do people cooperate with police in multi-ethnic societies? For scholars of comparative politics and international relations, examining the effects of ethnicity on patterns of conflict, cooperation, and state repression remains a foundational endeavor. Studies show individuals who share ethnicity are more likely to cooperate to provide public goods. Yet we do not know whether co-ethnic cooperation extends to the provision of law and order and, if so, why people might cooperate more with co-ethnic police off… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 47 publications
0
8
1
Order By: Relevance
“…Our results contradict recent findings from Liberia, where studies have either found that less powerful groups are treated worse by their coethnics (Blair et al, 2022) or have found no effect of shared identity (Karim, 2020). Our findings are instead closest to Curtice (2022), who finds in Uganda that citizens are less willing to report crimes to non-coethnic officers. While his explanation focuses on the police as a repressive arm of a semi-authoritarian state-hence highlighting citizens' fear of repression as a mechanism-our focus is on the fairness and tone of largely non-violent everyday interactions.…”
Section: Introductioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Our results contradict recent findings from Liberia, where studies have either found that less powerful groups are treated worse by their coethnics (Blair et al, 2022) or have found no effect of shared identity (Karim, 2020). Our findings are instead closest to Curtice (2022), who finds in Uganda that citizens are less willing to report crimes to non-coethnic officers. While his explanation focuses on the police as a repressive arm of a semi-authoritarian state-hence highlighting citizens' fear of repression as a mechanism-our focus is on the fairness and tone of largely non-violent everyday interactions.…”
Section: Introductioncontrasting
confidence: 99%
“…Table 2 shows that these differences are statistically significant at conventional levels. Importantly, respondents feel that coethnic police officers will treat them preferentially: coethnicity matters for citizen interactions with police not only out of fear of non-coethnics (as in Curtice, 2022) but also out of the expectation of positive, preferential treatment from coethnics. Analyses Note.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The social relationship between the police and the community also bears on citizen perceptions of whether police share their interests. Some research on policing posits that ethnicity can play a major role in shaping citizen trust and cooperation with the police (Curtice, 2019; Nanes, 2018), and a large body of work on the U.S. shows that minority groups are often targeted by police (Lundman & Kaufman, 2003). These groups also have less trust in police and therefore cooperate less (Tyler, 2005).…”
Section: Citizen Cooperation With the Policementioning
confidence: 99%
“… 3 Although conjoints have been used to examine public perceptions on policing (e.g., Curtice 2022), the method, to the best of our knowledge, has not been used with police officer samples. …”
mentioning
confidence: 99%